Volume 5: Materials Technology; CFD and VIV 2008
DOI: 10.1115/omae2008-57045
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds Number Dependence of Flexible Cylinder VIV Response Data

Abstract: The response amplitude and the non-dimensional frequency of flexible cylinder vortex-induced vibrations from laboratory and field experiments show significant trends with increasing Reynolds number from 103 to 2 * 105. The analysis uses complex data from experiments with wide variations in the physical parameters of the system, including length-to-diameter ratios from 82 to 4236, tension dominated natural frequencies and bending stiffness dominated natural frequencies, sub-critical and critical Reynolds number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…As seen in the figure it seems that the CF displacements in average are higher for Pipe 3 compared to Pipe2. This is in accordance with previous observations [3]. The results in Fig.…”
Section: Xsupporting
confidence: 83%
“…As seen in the figure it seems that the CF displacements in average are higher for Pipe 3 compared to Pipe2. This is in accordance with previous observations [3]. The results in Fig.…”
Section: Xsupporting
confidence: 83%
“…(28) is based on experimental forced vibrations of rigid cylinder in the range of 500oReo3.3 Â 10 4 , and it is presently unknown whether this formula continues to be valid at higher Re (Govardhan and Williamson, 2006). Nonetheless, based on recent experimental results of flexible cylinder, Swithenbank et al (2008) showed a significant trend of increasing amplitudes with Re up to 2 Â 10 5 . For this reason, it is herein assumed that Eq.…”
Section: Influence Of Reynolds Numbermentioning
confidence: 90%
“…With reference to recent large-scale or in situ experimental observations, some interesting aspects comprise the space/time sharing, switching and interaction of multiple modes in different lock-in or synchronization regimes along with the estimation of response amplitudes (Chaplin et al, 2005b;Jaiswal and Vandiver, 2007;Trim et al, 2005), the dependence of VIV on Reynolds number (Swithenbank et al, 2008), the influence of cylinder initial curvatures resulting in modal interactions (Hover et al, 1997a(Hover et al, , 1997b and the highly modulated responses (Chaplin et al, 2005b;Chasparis et al, 2009). These aspects will be discussed in this paper based on a low-order multi-mode model and numerical approach.…”
Section: A Bmentioning
confidence: 99%
“…A lot of the high Reynolds number data remains the proprietary information of the oil and gas companies that funded the experiments, and only a few published datasets are available to researchers. Furthermore, when attempting to compile enough data so as to span a reasonable Reynolds number range, one inevitably runs into the problem of comparing data from many different systems with different dynamic properties, instrumentation procedures, etc... To date, the most comprehensive study of the Reynolds number effects on flexible cylinders is the work of Swithenbank et al (2008) who compile and organize the A/D vs. Re number data from ten different datasets including laboratory and field experiments. This paper attempts to build on the past work by using data from recent experiments on flexible pipes where the Reynolds number range spans three orders of magnitude.…”
Section: ܴ݁ = ܷ ‫ܦ‬ ‫ݒ‬mentioning
confidence: 99%